Studi pemahaman dan kesiapsiagaan siswa SMA dan SMK di Balikpapan Utara terkait mitigasi bencana tanah longsor - Putri Naila; Andi Nureva Ramadhani; Carol Liudongi; Zorijal Adesi; Andi Marini Indriani (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2025)
Landslides are one of the most common natural disasters in Indonesia and can occur in almost all parts of the country, including in East Kalimantan, especially in Balikpapan City. The region is highly vulnerable to landslides, especially during the very heavy rainy season. This is due to the geographical conditions predisposing to landslides as well as high rainfall, which worsens soil stability. With the high potential risk of landslides, it is important to increase the awareness and understanding of the community, particularly the younger generation, on mitigation measures that can be taken to reduce the impact of this disaster. This research makes use of questionnaire distribution as a tool to analyse the level of awareness and understanding of SMA and SMK students in North Balikpapan regarding landslide mitigation. This approach provides a clearer picture of the extent to which students understand the causes, impacts, and mitigation measures that can be taken in dealing with landslides. The results of this study show that most of the students, 73.50%, agree that they know the main causes of landslides. This indicates that the majority of students have received information about the factors that cause landslides, such as heavy rain, erosion, or human activities that destroy vegetation. However, although this figure is quite high, there are still 26.50% of students who disagree or feel that they do not understand the main causes of this disaster, which reflects a lack of information or awareness among some students. In addition, the majority of SMA and SMK students in North Balikpapan have a good understanding of landslides, including their impacts and mitigation measures after disasters. Nevertheless, there are still a small number of respondents who do not fully understand some important concepts related to landslides, such as the mitigation steps that need to be taken before, during and after a disaster occurs. These findings provide useful insights for relevant parties, especially for schools and educational institutions, to continue improving socialisation and education on landslide mitigation.